HIV infection and professional confidentiality - Boroni, Valentina (Medicina e Morale, 1991)
The protection of the right to confidentiality is at stake at present because of HIV infection, where the rights of the individuai often contrast with the safeguarding of the well-being of others. In the present notes, the ethical argument for a non-absolute meaning of medical confidentiality and the different positions of the Italian and American Professional Deontology Codes about confidentiality are discussed. Particular attention is dedicated to the legal protection of the right to confuientiality in the Italian context, where we find as a general rule the prohibition of the disclosure of the medical secret but also cases in which the physician must disclose it and cases in which he can disclose it.